A screening identifies harmine as a novel antibacterial compound against Ralstonia solanacearum - Xia, Hongkai; Huang, Yanxia; Wu, Ruoyu; Tang, Xin; Cai, Jun; Li, Shun-xiang; Jiang, Lin; Wu, Dousheng (Frontiers in Microbiology, 2023)
Ralstonia solanacearum, the causal agent of bacterial wilt, is a devastating plant pathogenic bacterium that infects more than 450 plant species. Until now, there has been no efficient control strategy against bacterial wilt. In this study, we screened a library of 100 plant-derived compounds for their antibacterial activity against R. solanacearum. Twelve compounds, including harmine, harmine hydrochloride, citral, vanillin, and vincamine, suppressed bacterial growth of R. solanacearum in liquid medium with an inhibition rate higher than 50%. Further focus on harmine revealed that the minimum inhibitory concentration of this compound is 120 mg/L. Treatment with 120 mg/L of harmine for 1 and 2 hours killed more than 90% of bacteria. Harmine treatment suppressed the expression of the virulence-associated gene xpsR. Harmine also significantly inhibited biofilm formation by R. solanacearum at concentrations ranging from 20 mg/L to 60 mg/L. Furthermore, application of harmine effectively reduced bacterial wilt disease development in both tobacco and tomato plants.Collectively, our results demonstrate the great potential of plant-derived compounds as antibacterial agents against R. solanacearum, providing alternative ways for the efficient control of bacterial wilt.